REKAYASA DAN PENGUJIAN MESIN PEMBENTUK DAN PENGASAH PISAU PENCACAH LIMBAH PERTANIAN - Irma Fahrizal; Leo Dedy Anjiu; Erwin Erwin; Suhendra Suhendra (JURNAL CRANKSHAFT, 2026)
Shredding machines play a crucial role in agricultural waste processing. A common issue encountered was shredding efficiency, particularly due to the poor quality of the shredding blades. Currently, the process of shaping and sharpening shredding blades was still carried out traditionally, resulting in inconsistent cutting angles. Poor-quality blades result in high energy consumption and low-quality shredded output. To address these issues, a study was conducted aimed at developing a machine capable of integrating the blade forming and sharpening processes into a single system. This research phase includes mechanical engineering, machine performance testing, and analysis of test data. The observed data collected include cutting torque and improvements in cutting performance. The test material used was potato tubers. Based on the engineering results, the machine measures 70 cm in length, 30 cm in width, and 70 cm in height, and was powered by a 2 HP electric motor, with the forming and sharpening blades operating at 1,400 rpm. Based on the test results, after the shredding blades were formed and sharpened, the cutting torque was reduced from 14.85 N·m to 7.36 N·m. Other observations showed that there was an average increase in cutting performance of 50.30% after the blade forming and sharpening process was performed.